EFFECTS ON CHANGING PRACTICES OF FOOD USE OF PEOPLE IN 6 COMMUNITIES OF RED RIVER RIVER, THAI BINH PROVINCE AFTER INTERVENTION TO REDUCE ASEN RISK OF EXPOSURE (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the change of practice using food of people at six communes along theRed River in Thai Binh province after integrated communication interventions to reduce the risk ofarsenic exposure.Methods: A community intervention study on 1184 people aged ≥ 18 years.Results: The percentage of people who are aware of the signs of arsenic poisoning is low. Theproportion of people with correct knowledge and practice about the influencing factors of Arsenicpollution on health after the intervention was higher than before the intervention in both theintervention and control groups, however after the intervention group higher than the control groupwith p
Keywords: Arsenic, food use practice, communication intervention.